Total Antioxidant Capacity in the Muscle Tissue of Rainbow Trout (Oncorhynchus mykiss Walbaum) Under in Vitro Incubation with Leaf Extracts of Some Thymus (Lamiaceae) Representatives - Honcharenko, Vitaliy; Tkachenko, Halyna; Nachychko, Viktor; Prokopiv, Andriy; Osadowski, Zbigniew (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2018)
The aim of this study was to evaluate the in vitro effect of buffer extracts obtained from leaves of various representatives of Thymus genus on the total antioxidant capacity (TAC) of the muscle tissue of the rainbow trout (Oncorhynchus mykiss Walbaum). Leaves of Thymus serpyllum L. emend. Mill., Th. pannonicus All., Th. pulegioides L., Th. × porcii Borbás (a hybrid between Th. pannonicus and Th. pulegioides), Th. alpestris Tausch ex A. Kern. were harvested to study. Freshly collected leaves were washed, weighted, crushed, and homogenized in 0.1M phosphate buffer (pH 7.4) (in proportion 1:19, w/w) at ambient temperature. The supernatant of the rainbow trout muscle tissue was used to incubate with leaf extracts of various representatives from Thymus genus (in a ratio 19:1) at room temperature. The most potent antioxidant effect was demonstrated for the extracts of Th. alpestris, Th. × porcii, Th. pannonicus, Th. serpyllum, and Th. pulegioides compared to phosphate buffer control (59.5, 48, 45.9, 43.9, and 38.8 %, p<0.05, respectively). The results of this study provide a new perspective on the use of various Thymus species as a medicinal plant to improve the antioxidant response of rainbow trout. Further studies including the use of other medicinal plants as food additives in aquaculture, the assessment of its antioxidant effects on various tissues are in progress.